A Case Report with Severe Thrombocytopenia Induced by Axitinib - Ulkuhan I. Koksal; Janeiro Valle Goffin; Brian Lewis; Oliver A. Sartor; Elizaveta Belyaeva; Francisco Socola; Pedro C. Barata (Case Reports in Hematology)
Axitinib is an oral, second-generation tyrosine kinase inhibitor that is selective for vascular endothelial growth factor receptors (VEGFR). This agent is approved as monotherapy or in combination with immune checkpoint inhibitors for the treatment of metastatic renal cell carcinoma. Axitinib is associated with a safety profile very similar to other anti-VEGFR inhibitors but usually with fewer hematologic adverse events, due to the selectivity for VEGF. In this report, we presented a rare case of grade 4 axitinib-induced thrombocytopenia, not observed with other antiangiogenic therapies. We discuss the differential diagnostic work-up, the necessary multidisciplinary approach, and the successful management of the case.